2014
DOI: 10.1021/ma502000y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Iso-Selective and Active Catalysts of Sodium and Potassium Monophenoxides Capped by a Crown Ether for the Ring-Opening Polymerization of rac-Lactide

Abstract: Sodium and potassium complexes supported by a bulky monophenoxy with one xanthenyl group at the orthoposition and 18-crown-6 or 15-crown-5 as an auxiliary ligand were synthesized and characterized. These complexes are highly iso-selective and active catalysts for the controlled ringopening polymerization of rac-lactide. The best isotacticity (P m ) achieved was 0.86, which is the highest iso-selectivity reported to date for an alkali-metal complex. In addition, the corresponding polymer exhibited a high T m of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 124 publications
1
69
0
6
Order By: Relevance
“…To date, many good metal complexes have been used for the stereoselective ROP of rac-lactide, such as aluminium, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] indium, [23][24][25][26][27] zinc, [28][29][30][31][32][33] and other metal complexes. [34][35][36][37] In the past few years, we firstly reported some highly isoselective sodium/potassium complexes for the ROP of rac-lactide, [38][39][40][41][42] which is interestingb ecause sodium/p otassium metal ions are nontoxic and suitable for the synthesis of medical-related polylactide.N ormally the low Lewis acidity of sodium/potassium ion will cause the interactions betweens ubstrates be weak and the stereoselectivities of organic or polymerization reactions consequently are not very high;t he charm of coordinationc hemistry is that auxiliary ligands can construct ac onfined environmenta rounda ctives odium/p otassium ion centre and can synergistically improve the interactions betweenl igand, monomer,a nd polymer chains, then the stereoselectivities of sodium/potassium complexes can increase.I np revioush ighly isoselective sodium/potassium complex systems, the auxiliary ligands mainly focusedo nc rown ethers and one chargedb ulky phenol, andt he good isoselectivity even can reachtoP m = 0.94 at À70 8C. The crown ether ligands seem to be indispensable in previouss odium/potassium systemsf or high isoselectivities because of the confined space between crown ether and bulky substituted groups of phenol ligand.H owever,a...…”
Section: Introductionmentioning
confidence: 99%
“…To date, many good metal complexes have been used for the stereoselective ROP of rac-lactide, such as aluminium, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] indium, [23][24][25][26][27] zinc, [28][29][30][31][32][33] and other metal complexes. [34][35][36][37] In the past few years, we firstly reported some highly isoselective sodium/potassium complexes for the ROP of rac-lactide, [38][39][40][41][42] which is interestingb ecause sodium/p otassium metal ions are nontoxic and suitable for the synthesis of medical-related polylactide.N ormally the low Lewis acidity of sodium/potassium ion will cause the interactions betweens ubstrates be weak and the stereoselectivities of organic or polymerization reactions consequently are not very high;t he charm of coordinationc hemistry is that auxiliary ligands can construct ac onfined environmenta rounda ctives odium/p otassium ion centre and can synergistically improve the interactions betweenl igand, monomer,a nd polymer chains, then the stereoselectivities of sodium/potassium complexes can increase.I np revioush ighly isoselective sodium/potassium complex systems, the auxiliary ligands mainly focusedo nc rown ethers and one chargedb ulky phenol, andt he good isoselectivity even can reachtoP m = 0.94 at À70 8C. The crown ether ligands seem to be indispensable in previouss odium/potassium systemsf or high isoselectivities because of the confined space between crown ether and bulky substituted groups of phenol ligand.H owever,a...…”
Section: Introductionmentioning
confidence: 99%
“…The K1-C7 distance of 2.623(3)Å is within a normal range compared with the reported crown ether potassium phenoxide complexes. [94][95][96][97][98][99][100] The O(7)-C(15) distance of 1.289(5)Å is comparable with those in crown ether potassium complex bearing 2-(anthracen-9-yl) phenolate ligands.…”
mentioning
confidence: 69%
“…93 Recently Wu and co-workers reported that crown ether complexes of sodium and potassium mono-phenoxides exhibited high catalytic activity and high iso-selectivity for the ROP of rac-lactide. [94][95][96][97][98][99][100][101] However, the phenoxide ligands are required to have very bulky ortho-substituents on the aromatic rings to achieve good selectivity. [94][95][96][97][98][99][100][101] It is interesting to design simpler ligands to get high catalytic selectivity of complexes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The solution became very sticky quickly as the increase of [CL] 0 /[Zn] 0 ratio so that the magnetic stir bar was stuck. (6) 116.49 (5) The polymerization rate was so fast that the influence of substituent R at the benzimidazolyl-N atom on the activity was difficult to be detected; however, the different R produced PCLs with different number-average molecular weights (M n ) and PDIs even if the same reaction parameters were used. The catalytic systems kept highly active in a broad temperature range over 0e90 C; whereas, the higher reaction temperature resulted in lower M n and broader PDI of PCLs (entries 2, 5 and 6 in Table 2).…”
Section: Rop Of ε-Cl In the Absence Of Bnohmentioning
confidence: 99%